ASSOCIATION BETWEEN SERUM FERRITIN AND MARKERS OF MALNUTRITION, INFLAMMATION, ATHEROSCLEROSIS (MIA) IN HEMODIALYSIS PATIENTS - MEERA SHIVASHEKAR; SHYAM KRISHNAN M; SHYAM KRISHNAN M; W EBENEZER WILLIAM (International Journal of Pharma and Bio Sciences, 2013)
Measurements of the Malnutrition, Inflammation and atherosclerosis (MIA) parameters are predictors of the outcome in hemodialysis (HD) patients. Ferritin, used as a marker of iron status, is also a marker of inflammation by its acute phase reaction property. The aim of this study is to find the association between serum ferritin and markers of MIA in HD patients. The study included 42 HD patients, devoid of iron therapy and 26 age and sex matched controls. The biochemical parameters were assessed using autoanalyzer. Results showed that HD patients had higher levels of serum ferritin, transferrin, hsCRP and decreased albumin levels. The study revealed a significant correlation between ferritin and hsCRP and between ferritin and albumin in HD patients. It shows that level of ferritin, an acute phase reactant, is increased in HD patients devoid of iron therapy. This concludes that a strong association exists between serum ferritin and MIA markers in HD patients.